Islamic Law Thoughts: Father's Position as Heirther in Syāfi’īyah Jurisprudence and KUHPerdata - Wildan, T. (Ulul Albab: Jurnal Studi dan Penelitian Hukum Islam, 2022)
This study aims to answer the main problem, how the position of the father as the heir according to SyÄfiâ€™Ä«yah jurisprudence and KUHPerdata and why there is a difference in place between the two. This research is a library research study using a qualitative approach with a comparative descriptive method. The results show a difference in the father's position as the heir in SyÄfiâ€™Ä«yah jurisprudence and KUHPerdata. In SyÄfiâ€™Ä«yah jurisprudence, the father has a definite place as mentioned in Surat An-Nisaâ€™:11, namely as Å¼awil furÅ«á¸ when together with the descendants of the heirs both men and women, as' â€˜aá¹£abah if there are no children and as Å¼awil furÅ«á¸ and â€˜aá¹£abah when together with a daughter. The father is in the same position as the heir's descendants without being hindered by any heir. While KUHPerdata father's position as the heir is classified in group II, the new father has the right if the heir of the first group no longer exists. The father does not become an heir and the descendants of the heir because the father is equated with a brother even though the father is in the first degree, which is the same as the descendants of the heirs.